International Student Strategy of Turkey: Analysis of The Present Situation and Suggestions for The Solutions of The Problems - Kürtül, İbrahim and Kapağan, Enver and Kundakçı, Mustafa and Bacaklı, Yılmaz (Journal of History Culture and Art Research, 2021)
Since knowledge today is the most powerful core source for individuals, society and states, it is becoming an essential leverage that affects profoundly the dynamics of all parties. For this reason, information gains a nature that will affect all dynamics of individual and social life. Moreover, the fact that there is no boundary for knowledge is very convenient for states that want to expand their power and efficiency. Due to that, they allocate a huge number of resources on producing knowledge. Commercializing the strategic knowledge is also an affirmative determinant for this allocation. Higher education institutions are places where qualified information is processed and transferred. For this reason, it is only possible to reach qualified information by receiving education in higher education institutions that provide this service under appropriate conditions. The transformation of knowledge into a basic need for people and societies today significantly increases the demands for higher education. In countries that develop higher education institutions with their investments, the demands for these institutions are increasing day by day not only by the citizens of the countries but also by international students who cannot access qualified information in their countries for various reasons. In this sense, Turkey has become a centre of attraction in higher education seriously. It is vital for Turkey to successfully implement perpetually the Internationalization Strategy Document in Higher Education to meet fast increasing international student demands. This paper makes an effort to review the current situation of the internationalization strategy of higher education in Turkey, summarize its implementation, emphasize problems encountered, and propose very essential suggestions for the solutions of these problems. It will surely help Turkey’s effort to reach its target on the internationalization strategy of higher education, and to become an important centre of attraction for both international students and academic staffs. As suggested in this paper, this aim is acquired only under the condition of identifying problems, making decisions very fast for the solutions, and prosecuting the implementation of the decisions continuously.